Human-caused increases in reactive nitrogen burial in sediment of global lakes - Mei Wang (Elsevier, 2021)
Summary: Human activities have increased reactive nitrogen (Nr) input to terrestrial ecosystems compared with the pre-industrial era. However, the fate of such Nr input remains uncertain, leading to missing sink of the global nitrogen budget. By synthesizing records of Nr burial in sediments from 303 lakes worldwide, here we show that 9.6 ± 1.1 Tg N year−1 (Tg = 1012 g) accumulated in inland water sediments from 2000 to 2010, accounting for 3%–5% of global Nr input to the land from combined natural and anthropogenic pathways. The recent Nr burial flux doubles pre-industrial estimates, and Nr burial rate significantly increases with global increases in human population and air temperature. Sediment ratios of C:N decrease after 1950 while N:P ratios increase over time due to increasingly elevated Nr burial and other related processes in lakes. These findings imply that Nr burial in lakes is overlooked as an important global sink of Nr input to terrestrial ecosystems. Public summary: • Ten million tons of nitrogen was buried in lake sediment annually during 2000–2010 • Lake nitrogen burial rate is increasing since the 1860s • Nitrogen burial is highly correlated with carbon burial rate in lakes • Nitrogen burial in lakes can explain part of the global missing nitrogen sink